2013
DOI: 10.3389/fimmu.2013.00253
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and Thymic Foxp3+ Regulatory T Cells in Search of Origin, Distinction, and Function

Abstract: Over the past decade, much has been learnt and much more to discover about Foxp3+ regulatory T cells (Tregs). Initially, it was thought that Tregs were a unique entity that originates in the thymus. It is now recognized that there is a fraternal twin sibling that is generated in the periphery. The difficulty is in the distinction between these two subsets. The ability to detect, monitor, and analyze these two subsets in health and disease will provide invaluable insights into their functions and purposes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 131 publications
(145 reference statements)
1
62
0
1
Order By: Relevance
“…Although Nrp-1 was initially proposed as a naturally occurring T reg -cell-specific marker (14,17), additional studies have shown that peripherally induced T reg cells are capable of up-regulating Nrp-1, especially in the lung (18,19). Consequently, it remains uncertain whether the expanded T reg cells in the lungs of BeOexposed HLA-DP2 Tg mice are naturally occurring or peripherally induced.…”
Section: Discussionmentioning
confidence: 96%
“…Although Nrp-1 was initially proposed as a naturally occurring T reg -cell-specific marker (14,17), additional studies have shown that peripherally induced T reg cells are capable of up-regulating Nrp-1, especially in the lung (18,19). Consequently, it remains uncertain whether the expanded T reg cells in the lungs of BeOexposed HLA-DP2 Tg mice are naturally occurring or peripherally induced.…”
Section: Discussionmentioning
confidence: 96%
“…Considering the importance of T regulatory cells and distinct role of their subsets substantial effort was made to detect and analyze thymus derived and peripheral Tregs. Several potential discriminating markers were identified, among them Helios was most thoroughly investigated [4].…”
Section: Discussionmentioning
confidence: 99%
“…nTregs are thymus derived regulatory cells with a proposed role in central tolerance, while iTregs are induced in the periphery [3]. As the field of Tregs is still evolving, there are some subtle differences in nomenclature, for example Tregs derived in periphery are also named pTregs (for review see [4]). So far there are no reliable markers how to distinguish these subpopulations of Treg cells.…”
Section: Introductionmentioning
confidence: 99%
“…A major limitation in the study of regulatory T cells is a lack of specific cell surface markers, particularly in humans . Foxp3 is a widely accepted marker of many regulatory T‐cell populations, but is intracellular so cells must be permeabilized in order to perform staining, which limits the isolation of pure and live cells.…”
Section: Discussionmentioning
confidence: 99%